Jesus of Nazareth. Part two, Holy week : from the entrance into Jerusalem to the Resurrection - Benedict XVI, Pope (San Francisco Calif. : Ignatius Press, 2011)
Offers a detailed analysis of Jesus Christ's final week in Jerusalem, examining the political, religious, and scholarly aspects of Jesus' life, teaching, death, and resurrection.
Keywords: Jesus Christ -- Biography. Jesus Christ -- Person and offices. Jesus Christ -- Historicity